2016
DOI: 10.1016/j.ecolind.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated ozone on physiological, anatomical and ultrastructural characteristics of four common urban tree species in China

Abstract: a b s t r a c tFast urbanization has led to ozone (O 3 ) being the main pollutant in summer in most of China. To assess future ground-level O 3 effects on the service of urban greening species and clarify the underlying mechanism of O 3 damage, four common urban greening species, Ailanthus altissima (AA), Fraxinus chinensis (FC), Platanus orientalis (PO) and Robinia pseudoacacia (RP) were exposed to non-filtered air (NF) and to elevated O 3 (E-O 3 ) in open-top chambers. E-O 3 induced visible injury in all sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 49 publications
4
18
0
3
Order By: Relevance
“…The first paper on O 3 impacts on Chinese woody species was published in 2006 (He, Ruan, Chen, & Lu, 2006). Since then, more than 60 experimental studies have been carried out in southern and northern China to investigate O 3 effects on woody species native of China or largely cultivated in China-e.g., for ornamental and greening purposes-in terms of gas exchange, chlorophyll a fluorescence, antioxidant system, and growth (e.g., Feng & Li, 2017;Feng et al, 2011;Gao, Catalayud, García-Breijo, Reig-Armiñana, & Feng, 2016;He et al, 2007;Xu, He, Chen, Su, & Huang, 2014;Yan et al, 2010).…”
mentioning
confidence: 99%
“…The first paper on O 3 impacts on Chinese woody species was published in 2006 (He, Ruan, Chen, & Lu, 2006). Since then, more than 60 experimental studies have been carried out in southern and northern China to investigate O 3 effects on woody species native of China or largely cultivated in China-e.g., for ornamental and greening purposes-in terms of gas exchange, chlorophyll a fluorescence, antioxidant system, and growth (e.g., Feng & Li, 2017;Feng et al, 2011;Gao, Catalayud, García-Breijo, Reig-Armiñana, & Feng, 2016;He et al, 2007;Xu, He, Chen, Su, & Huang, 2014;Yan et al, 2010).…”
mentioning
confidence: 99%
“…, Scoffoni et al 2016). In addition, due to the fact that symptoms are rarely observed in leaf veins under O 3 stress (Zhang et al 2012, Gao et al 2016, it can therefore be inferred that the reduction in K leaf mainly occurs in mesophyll cell where the major resistance to water flow is located (Sack and Holbrook 2006, Sack and Scoffoni 2013, Scoffoni et al 2016).…”
Section: Ozone Impacts On Plant Hydraulics and Water Loss Controlmentioning
confidence: 99%
“…In this study, plant photosynthetic performance was weakened under O 3 stress, as indicated by the decline in leaf chlorophyll content (Figure 4), requiring more biomass to be allocated to the shoot in order to maintain high levels of photosynthesis. Additionally, O 3 stress obstructs phloem sieve elements by increasing the accumulation of callose, consequently hampering assimilate transport from shoot to root (Calatayud et al, 2011;Gao et al, 2016). Moreover, O 3 stress stimulates the root respiration rate, as suggested by Nouchi et al (1991) and Thwe et al (2013), which subsequently accelerates the consumption of root biomass.…”
Section: Elevated O 3 Levels Inhibit the Productivity Of Flowering Plmentioning
confidence: 99%